Gauging customers' negative disconfirmation in online post-purchase behaviour: The moderating role of service recovery - Muhammad Mazhar; Ding Hooi Ting; Amir Zaib Abbasi; Muhammad Aamir Nadeem; Haider Ali Abbasi (Cogent Business & Management, 2022)
Negative disconfirmation will usually lead to switching behaviour and attenuate customers' repurchase intentions, a behaviour that will undercut businesses' profitability. Limited research discussed post-purchase behaviour, in general, and how to retain aggrieved customers during the online shopping experience, in particular. This study investigates the observed behavioural outcome of Malaysian customers in online shopping with regard to customers' future buying decisions who faced disconfirmation during the pandemic. Specifically, this study aims to examine service recovery as a moderator that can potentially alleviate the adverse effect of negative disconfirmation on repurchase intention and switching intention. Online questionnaires were distributed. 331 valid data were collected from customers using Smart PLS 3.3.2. The results showed that negative disconfirmation is negatively associated with repurchase intention and positively affects the switching intention. The moderating effect of service recovery demonstrated a significant positive impact on switching and repurchase intention. The empirical findings will enrich the literature on service recovery, consumer behaviour, and service management, and provide suggestions for webstores in terms of customers' engagement that can apt recovery response process after customers' complaints. Lastly, limitations and future directions are discussed for scholarly attention.
Keywords: 650; repurchase intention; negative disconfirmation; Online shopping; service recovery; switching intention